Vision and environmental habits of high school students /Visão e hábitos ambientais de discentes do ensino médio da Escola Estadual Professor Mileno Ferreira da Silva no município de Santana do Ipanema. - Romenito Guilherme de Melo (Universidade Estadual de Alagoas, 2016)
Environmental issues are increasingly topics covered mainly by the media seeking to show the importance of awareness and preservation of natural resources, thus showing the consequences of the aggression suffered by nature that has accumulated over the years leaving behind polluted rivers, lack rain, global warming, waste that becomes a big problem, desertification, deforestation and fires. This study aimed to analyze the habits and environmental vision of a group of students from 1st to 3rd grade high school of a state school in Santana do Ipanema district, in addition to seeking to understand which way the environmental reporting has contributed in the formation of critical / environmental sense of the students. The research was done through the application of thirty (30) structured questionnaires with ten (10) questions focused on the theme, eight closed and two open where one of the open asked to which reflect the environmental reality of where they reside. The students were randomly selected and data collected computed in Word / Excel 2013. It was found that there is still confusion among students to define what would be the environment, while it is perceived to possess habits, however small, that harm the environment. Clearly the lack of information for many environmental issues, but it is already possible to notice that begins to sprout the seed of awareness